Comparison of informational vs. energetic masking effects on speechreading performance - Lidestam, Björn; Holgersson, Johan; Moradi, Shahram (Frontiers in Psychology, 2014)
The effects of two types of auditory distracters (steady-state noise vs. four-talker babble) on visual-only speechreading accuracy were tested against a baseline (silence) in 23 participants with above-average speechreading ability. Their task was to speechread high frequency Swedish words. They were asked to rate their own performance and effort, and report how distracting each type of auditory distracter was. Only four-talker babble impeded speechreading accuracy. This suggests competition for phonological processing, since the four-talker babble demands phonological processing, which is also required for the speechreading task. Better accuracy was associated with lower self-rated effort in silence; no other correlations were found.